Pollution and Health Risk Assessment of Heavy Metals in Farmlands and Vegetables Surrounding a Lead-Zinc Mine in Yunnan Province, China. Issue 4 (19th May 2022) - Lai, Li; Li, Bo; Li, Zu-ran; He, Yong-mei; Hu, Wen-you; Zu, Yan-qun; Zhan, Fang-dong
ABSTRACT: To investigate the contaminant characteristics of heavy metals in soils and vegetables surrounding a lead-zinc mine in Huize County, Yunnan Province, thirty surface soil samples and vegetable samples were collected to measure the contents of heavy metals, including lead (Pb), zinc (Zn), copper (Cu), and cadmium (Cd). The potential risk was evaluated by using the single factor pollution index, Nemerow comprehensive pollution index, and target hazard index. The results showed that the contents of Pb, Zn, Cu, and Cd in the soil were 954.1, 2236.5, 151.1, and 4.83 mg·kg −1, respectively. Compared with the soil background values in Yunnan Province, the soil surrounding the lead-zinc mine was polluted by Pb, Zn and Cd. The Nemerow comprehensive pollution index evaluation indicated that the soil was heavily polluted. The contents of Pb, Zn, Cu, and Cd in vegetables were 117.5–778.6, 430.3–2212.4, 16.8–89, and 1.28–34.3 mg·kg −1, respectively. Among them, the contents of Pb and Cd in vegetables exceeded the pollutant limit in food products of China's National Standard for Food Safety (GB 2762–2017). The contents of Pb, Zn and Cd in the soil were extremely significantly or significantly correlated with the contents of Pb, Zn and Cd in the edible parts of vegetables. The results indicated that there was serious heavy metal pollution and significant health risk for the soil and vegetables surrounding the lead-zinc mine. The research results not only reveal the contaminant characteristics of heavy metals in soils and vegetables surrounding a lead-zinc mine in Huize County, Yunnan Province, but also could provide a scientific evidence for reasonable utilization and ecological remediation.